The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.virol.2008.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of different chicken lines to H7N1 highly pathogenic avian influenza virus and the role of Mx gene polymorphism coding amino acid position 631

Abstract: Five chicken lines were experimentally infected with a HPAI H7N1 virus, to examine the variation in susceptibility to infection. Three lines showed high susceptibility to the virus, while two showed some resistance, with 7 out of 20, and 11 out of 15 birds, respectively, remaining healthy and surviving the experimental infection. Genotyping for the G/A polymorphism at position 2032 of Mx cDNA showed that one line was fixed for the G allele, and two were segregating for A and G alleles. Birds in the other two l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 24 publications
4
44
0
Order By: Relevance
“…In a previous study, Sironi et al (2008) initially observed discrepancies in genotyping data obtained from sequencing and PCR-RFLP approaches. That was the result of an A/G single nucleotide polymorphism in the F primer used in PCR-RFLP.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study, Sironi et al (2008) initially observed discrepancies in genotyping data obtained from sequencing and PCR-RFLP approaches. That was the result of an A/G single nucleotide polymorphism in the F primer used in PCR-RFLP.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, 85 chickens from three commercial broiler lines and two experimental lines (New Hampshire and White Leghorn) were genotyped with both the PCR-RFLP protocol described here and sequencing. Full identity of results between the two methods was obtained for each of the 85 chickens (Sironi et al, 2008). Forty-two broilers from six other commercial broiler lines were spe- cifically genotyped for the present paper.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations